POLITIK HUKUM KOPERASI DI INDONESIA (TINJAUAN YURIDIS HISTORIS PENGATURAN PERKOPERASIAN DI INDONESIA) - Muhammad Adib Zain (Fakultas Hukum Universitas Gadjah Mada, 2015)
AbstractThis study aimed to analyze the legal political of cooperative regulations of various period in Indonesia. This research is a normative law with secondary law materials. Based on the research, it can be argued that the existence and development of cooperatives have ups and downs in the political policy of thelaw in Indonesia. During the colonial period the cooperative regulation just set that cooperative is exist and make a cooperatives as one of the businesses. After the independence of Indonesia, the purpose of the cooperative is a popular economic movement which is expected to distribute prosperity equally. Unfortunatelly, cooperatives in the regime of the old order and the new order be used as a political tool to perpetuate the power of government. In the reform period, the cooperative regulation is worse because made cooperative like a company that pursues profit. IntisariPenelitian ini bertujuan untuk mengkaji politik hukum pengaturan koperasi dari berbagai zaman di Indonesia. Penelitian ini merupakan penelitian hukum normatif dengan bahan hukum sekunder. Berdasarkan penelitian dapat dikemukakan bahwa keberadaan dan perkembangan koperasi mengalami pasang surut dalam kebijakan politik hukum di Indonesia. Pada masa penjajahan pengaturan koperasi hanya sekedar mengatur koperasi ada dan menjadikan koperasi sebagai salah satu pelaku usaha. Pada masa kemerdekaan, tujuan adanya koperasi adalah sebagai gerakan ekonomi rakyat yang diharapkan mampu memeratakan kesejahteraan. Sayangnya koperasi dalam rezim orde lama dan orde baru dijadikan alat politik untuk melanggengkan kekuasaan pemerintah. Pada masa reformasi, pengaturan koperasi semakin buruk sebab menjadikan koperasi layaknya perusahaan yang mengejar keuntungan semata.